Hepatoprotective and anti-inflammatory effects of a standardized pomegranate (Punica granatum) fruit extract in high fat diet-induced obese C57BL/6 mice. (19th May 2021) - Pfohl, Marisa; DaSilva, Nicholas A.; Marques, Emily; Agudelo, Juliana; Liu, Chang; Goedken, Michael; Slitt, Angela L.; Seeram, Navindra P.; Ma, Hang
Abstract: Diets rich in fats are linked to elevated systemic inflammation, which augments the progression of inflammatory-related disorders including non-alcoholic fatty liver disease (NAFLD) and neurodegenerative diseases. A phenolic-enriched pomegranate fruit extract (PE) was investigated for its hepatoprotective and anti-inflammatory effects in male C57BL/6 mice fed either a high-fat diet or a standard rodent diet with or without 1% of PE for 12 weeks. Mouse livers and hippocampi were evaluated for the expression of genes associated with NAFLD and inflammation by multiplexed gene analysis. PE alleviated diet-induced fatty liver and suppressed hepatic lipid regulating genes including Cd36, Fas, Acot2 and Slc27a1 . In addition, PE suppressed gene expression of pro-inflammatory cytokines including Il-1α, Il-7, Il-11, Ifnα, Tnfα and Lepr in the hippocampi. Our findings support the protective effects of PE against high-fat diet-induced hepatic and neurological disease. Graphical Abstract: